KUALITAS PERAIRAN SUNGAI ULAR KABUPATEN DELI SERDANG SUMATERA UTARA Water Quality in the River Ular Deli Serdang, North Sumatera Province - Theresia Jilfiola S; Hasan Sitorus; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
River ecosystems is very important for human life because provide water for human activities such as agriculture, fisheries, industry and domestic. Community activities of agricultural and sand mining activities in the River Ular can be a source of water pollutant that which affect on water quality parameters of physics, chemistry and biology. Water had been studied and compared to the Quality Standard Government Decree No.82 of 2001 by using Storet method. The research was conducted in June 2014 through August 2014 along the River ular from Deli Serdang district boundary to the mouth of the river ular in Muara Pantai Indah. Measurement of water quality parameters was done at 3 stations with 3-point decision. The method used in the determination of water quality sampling station was purposive random sampling. River Ular water quality parameters based on chemicall physics with methods storet showed polluted water to moderate polluted condition. The highest a bundance of plankton found at agricultural area sand the lowest at estuary area. Plankton diversity index values was moderate, low uniformity and there is not dominant species. River Ular water quality based water quality standards according to Regulation No.82 of 2001can be utilized for the fish farming and agriculture to the designation of class III and IV.Keywords: Water quality parameter, Standards Regulation, Storet Method, River Ular